2012
DOI: 10.5433/1679-0359.2012v33supl2p3279
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da fitase no desempenho e na qualidade da carne de frangos de corte

Abstract: ResumoForam avaliados os efeitos da enzima fitase sobre o desempenho, o rendimento de carcaça e a qualidade da carne (oxidação lipídica dos músculos da coxa a e peito) de frangos de corte submetidos a dietas formuladas à base de milho, farelo de soja e farelo de gérmen de milho desengordurado (FGMD), um ingrediente com alta concentração de ácido fítico. Foram utilizados 300 frangos de corte machos, com quatro dias de idade, distribuídos em um delineamento experimental inteiramente casualizado, com três tratame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
0
1
Order By: Relevance
“…Studying the inclusion of different phytases in broiler diet, Wu et al (2015) found no differences for poultry viability during the period of 1-21 days, however, P levels were not reduced. Moreover, our performance results also differed from the findings of Brunelli et al (2012), who did not find differences between groups supplemented or not with phytase, however, these authors did not include the value of the enzyme in the nutritional matrix, and used the enzyme without reducing AP. On the other hand, Laurentiz et al (2009) also found a reduction in weight gain during the final period of broiler rearing when P levels were reduced without the use of phytases.…”
Section: Discussioncontrasting
confidence: 99%
“…Studying the inclusion of different phytases in broiler diet, Wu et al (2015) found no differences for poultry viability during the period of 1-21 days, however, P levels were not reduced. Moreover, our performance results also differed from the findings of Brunelli et al (2012), who did not find differences between groups supplemented or not with phytase, however, these authors did not include the value of the enzyme in the nutritional matrix, and used the enzyme without reducing AP. On the other hand, Laurentiz et al (2009) also found a reduction in weight gain during the final period of broiler rearing when P levels were reduced without the use of phytases.…”
Section: Discussioncontrasting
confidence: 99%
“…Differing from the results found in the present study, a study evaluating two levels of phytic phosphorus (0.22% and 0.44%) and three concentrations of phytase (0, 500, and 1000 FTU/kg of feed) in broiler diets showed that phytase improved the weight gain of broilers [ 32 ], although there was no difference between the two levels of phytic phosphorus studied. In agreement with the results in the current experiment, a study using two diets supplemented with phytase (750 FTU/kg and 1500 FTU/kg of feed) showed no effect on the body weight gain of broilers [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…This difference may have been more noticeable in the initial feeding phase because broilers have a greater food voracity in the finishing stage. Corroborating the results of our study, no differences in the FI were observed when broilers diets were supplemented with phytase at 750 FTU/kg or 1500 FTU/kg [ 33 ].…”
Section: Discussionsupporting
confidence: 68%